Structural Analysis And Design Of Steel-Framed House With Cold-Formed And Hot-Finished Rectangular Hollow Section - Naaim, Nurfarhah (2019)
This study presents the structural behaviour of cold-formed steel framing system for affordable housing. The objectives are carried out to study the behaviour of cold-formed steel structural framing system incorporating lightweight load bearing wall and slab and to compare the weight of the material used on the cold-formed steel structural of affordable housing. Four types of model that consist 243 members are used to analyse the steel structural framing system. Model 1 is cold-formed steel structural framing system and Model 2 is hot-finished steel structural framing system. Both of steel structures utilizing lightweight wall panel and lightweight composite slab. Model 3 and Model 4 are also cold-formed steel structural framing system and hot-finished steel structural framing system. Both of this structures using the different materials of walls and slab which are brick wall and precast reinforced concrete. All of the models are drawn in AutoCAD and analysed using STAAD.Pro software. This study found that the thinner of steel section can increase the value of deflection. The increasing of the member length and ratio of slenderness will decrease the buckling resistance. When the applied load increases, the buckling deformation is also increase. Besides that, the decreasing of the shear resistance is caused by the decreasing of the shear area. The thicker section and the lightweight material used can decrease the torsional rotation value. Other than that, the weight comparison of the steel structure shows that cold-formed steel structure with lightweight wall panel and lightweight composite slab is the best model due to light weight and more benefits for affordable housing.